Answer:
72.5
Step-by-step explanation:
Answer:
hexagon
Step-by-step explanation:
i g
Answer:
Donna-71
Martina-62
Martina's sample
It has the smaller mean
Step-by-step explanation:
I apologize if this answer is incorrect but I think this is right.
Answer:
final answer is 6
Step-by-step explanation:
Given ![f(x)=6x-2](https://tex.z-dn.net/?f=f%28x%29%3D6x-2)
To find the difference quotient use formula
![\frac{f(x+h)-f(x)}{h}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%2Bh%29-f%28x%29%7D%7Bh%7D)
![f(x)=6x-2](https://tex.z-dn.net/?f=f%28x%29%3D6x-2)
![f(x+h)=6(x+h)-2=6x+6h-2](https://tex.z-dn.net/?f=f%28x%2Bh%29%3D6%28x%2Bh%29-2%3D6x%2B6h-2)
Now plug it in the formula
![\frac{f(x+h)-f(x)}{h}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%2Bh%29-f%28x%29%7D%7Bh%7D)
![\frac{6x+6h-2-(6x-2)}{h}](https://tex.z-dn.net/?f=%5Cfrac%7B6x%2B6h-2-%286x-2%29%7D%7Bh%7D)
![\frac{6x+6h-2-6x+2)}{h}](https://tex.z-dn.net/?f=%5Cfrac%7B6x%2B6h-2-6x%2B2%29%7D%7Bh%7D)
![\frac{6h}{h}](https://tex.z-dn.net/?f=%5Cfrac%7B6h%7D%7Bh%7D)
6
Answer:
first thing to do is get up from your sit and go cry because that question is to hard